Soft power of frugal innovation and its potential role in India's emergence as a global lead market for affordable excellence - Rajnish Tiwari; Jaideep Prabhu (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2018)
The phenomenon of frugal innovation, as characterized by "affordable excellence", is experiencing increasing acceptance by business leaders, policy makers and scholars around the world. Frugal products, services and technologies strive to radically increase affordability while significantly reducing their environmental footprint through careful and prudent use of resources. It is expected that frugal solutions will be increasingly necessary in both the developed and developing world to ensure social inclusion, environmental sustainability and continued economic growth. Traditionally, frugality has been regarded as a social virtue in India and the socio-cultural context of the country provides a fertile environment for the development of frugal products and services. Not surprisingly, considerable research shows that discussions of frugal innovations have been closely associated with India. This concept has now begun to spread to other developing and industrialized nations. A primary objective of this conceptual paper is to showcase how frugal innovations emanating from India have found acceptance in other corners of the world and why they contribute to India's soft power on a global stage. We argue that frugal innovations can potentially provide a useful medium for a benevolent power that aims to promote peaceful coexistence, inclusive growth and prosperity around the world. Indian firms and policymakers should not become complacent about their existing businesses and fail to comprehend the importance of frugal innovation. They would be well advised to retain their focus on creating customer value and avoid falling prey to the dominant logic of potentially wasteful, unsustainable and exclusive innovation approaches. Instead of focusing on delivering "more for more for few" they should rather continue to focus on delivering "more for less for many". The demand for affordable and sustainable excellence is sure to grow globally and India can establish itself as a global soft power in the process.
urn:nbn:de:gbv:830-88222389
Keywords: 330; Frugal Innovation; Lead Markets; Resource-constrained Innovation; Reverse Innovation; Soft Power; Frugality; Culture